Arab Republic of Egypt Urban Sector Note : Volume 2. Towards An Urban Sector Strategy - World Bank (Washington, DC, 2014)
The objective of this paper is to present a succinct and up-to-date review of the urban sector in Egypt, with a focus on issues for which there is new insight or emerging government interest. The two main themes of the report are the challenges facing the urban sector and the policy implications at various levels of government. Some of the reports mains findings are: urbanization in Egypt takes on forms and processes which are not well understood and as a consequence urban policies are sometimes weak or counter productive; until now policies and actions in the urban sector have mainly consisted of State driven, supply-side interventions; due to the focus on development in the desert, the dynamics of urbanism in the Nile Valley and Delta, which together contain over 95 percent of the country's population, have largely been ignored; and finally it is rare that government of Egypt's urban development projects include a strategy of capturing the appreciation value of their investments ("unearned increment"), cross-subsidization or cost recovery. The note concludes with a set of recommendations of ways to improve the government's response to the urban challenge.